Securitization: a financing vehicle for all seasons? - Bonnie G. Buchanan (Bank of Finland, 2016)
Securitization is considered to be one of the biggest financial innovations of the last century. It is also regarded as both a catalyst and solution to the 2008 financial crisis. Once a popular method of financing the mortgage and consumer credit markets, aspects of the global securitization market are now struggling to revive. In this paper I discuss the role that ethics played in securitization prior to the 2008 financial crisis and find that it is not an obvious story of moral failures, but rather that it lies in more subtle elements of the financial system. The ethics uncertainty role in the securitization story is one of flawed incentives and the shifting of responsibility for handling risk. The role of securitization and the ethics of risk transfer have rarely been discussed explicitly in the literature. The historical origins of securitization and lessons learned from previous flawed uses of the process are also provided. I also detail the various global institutional reform proposals that have taken place. Moving forward, it is crucial to understand the causes, consequences and ethical implications of securitization in the financial crisis so as to help individuals and managers better assess risk, align incentives and design appropriate policy responses.
URN:NBN:fi:bof-201612151537
Keywords: A1; F3; G1; G2; G21; G23; G24; G28; 330